Vitamin D and Hypertension - Wang, MD, PhD, Lu (North American Journal of Medicine and Science, 2009)
Early experimental studies have suggested that vitamin D may be involved in the regulation of blood pressure (BP) and the pathogenesis of hypertension through its effects on calcium homeostasis, vascular smooth muscle cells and endothelial cells, and activity of the renin-angiotensin system (RAS). Human studies have shown a possible link between inadequate vitamin D status and elevated BP or higher prevalence of hypertension. Due to limited data from well-designed prospective studies, it remains unsettled whether low vitamin D status leads to future risk of hypertension. The BP-lowering efficacy of high-dose vitamin D supplementation for hypertension prevention must be tested in future randomized clinical trials.